Pemberian Edukasi Kesehatan Reproduksi dengan Menggunakan Media Film pada Remaja di Puskesmas Kota Cirebon - Elfi, Elfi; Padmawati, Rinela (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2021)
Film is one of teaching and learning interaction tools that combines two kinds of sense organs at the same time in helping the learning process. Film media can increase the knowledge of school dropout adolescents about the adolescent reproductive health. (Elfi, Rinela P, 2019). Nowadays, adolescents can easily access the internet via smartphones, so that it can have a negative impact on using the internet. Community Service Activities are carried out to provide education on reproductive health education including the information on female / male reproductive organs, puberty, sexual behavior and genitalia hygiene through film. The method of implementation is film screening to assess the level of knowledge and attitudes of adolescents before and after screening. The target of this activity is adolescents aged 15 to 19 years in the Work Area of Puskesmas Majasem, Cirebon City The results showed an increase in the knowledge and attitudes of adolescents after given the health education about reproductive health through film. Counseling using well-packaged film can increase adolescent interest, so that can increase adolescent knowledge and attitudes. Keywords: Film, knowledge, attitudes